Analisis Determinan Ketepatan Waktu Pelaporan Keuangan Perusahaan Manufaktur - Adila Ayu Sukma; Sartika Wulandari; Widhian Hardiyanti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study examines the effect of managerial ownership, institutional ownership, independent commissioners, audit committees and profitability, on the timeliness of financial reporting in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The population in this study were all companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sample selection used the purposive sampling method and 299 samples were obtained. The analysis used is logistic regression analysis. The results showed that profitability had a significant positive effect on the timeliness of financial reporting. Meanwhile, managerial ownership, institutional ownership, independent commissioners, and audit committees have no effect on the timeliness of financial reporting